The Intensifiers on Makasae and English Languages - António Constantino Soares; Atánasio António Gusmáo Freitas Belo (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This research aimed to investigate the intensifiers on Makasae and English languages. This topic was sellected in order to find out the similarities and differences of using intensifiers on both Makasae and English languages. Typologically, both Makasae and English languages have different word order syntactically. This research applied qualitative method which also involves annotating transcripts or written texts to highlight and explain the use of intensifiers and their effects on meaning. Direct Elicitation was used by providing the examples of sentences used, including the specific intensifiers. The other technique used is sentence completion tasks which aimed to complete incomplete sentences by filling in the gaps with appropriate intensifiers. After all the data collected, then they were analysed qualitaitvely by using deletetion and reduction techniques.